Analisis Kebutuhan Model TIL (The Information Literacy) Tipe The Big Six berbasis Digital untuk Pembaca Semenjana Sekolah Dasar - Dewi, Annisa Anita; Karlimah, Karlimah; Apriliya, Seni (PAKAR Pendidikan, 2025)
This study aims to analyze the need for developing a digital-based information literacy model, specifically the TIL (The Information Literacy) Model of The Big Six type, designed for fifth-grade elementary school students categorized as intermediate readers. In the current era of digital disruption, where the flow of information is massive, rapid, and not always based on verified facts, information literacy becomes a fundamental skill. Students are often exposed to unfiltered information, which can lead to confusion, misinterpretation, and difficulty in distinguishing factual content from opinion or misinformation. This research employed a qualitative approach using ethnographic methods. Data collection techniques included semi-structured interviews, participatory observation, and documentation involving teachers and students. The findings reveal that students struggle to understand informational texts critically, lack familiarity with effective strategies to access relevant information, and are constrained by limited infrastructure and digital tools. Therefore, the development of a digital-based Big Six TIL Model is considered essential as a structured and contextualized learning approach. This model helps students build critical thinking, information selection, and analytical skills, thereby improving their overall literacy competence. Moreover, integrating digital literacy through this model enhances students’ motivation, supports 21st-century skill development, and prepares them to navigate the digital information landscape more responsibly and independently.